2007
DOI: 10.1515/bc.2007.077
|View full text |Cite
|
Sign up to set email alerts
|

Importance of tRNA interactions with 23S rRNA for peptide bond formation on the ribosome: studies with substrate analogs

Abstract: The major enzymatic activity of the ribosome is the catalysis of peptide bond formation. The active site -- the peptidyl transferase center -- is composed of ribosomal RNA (rRNA), and interactions between rRNA and the reactants, peptidyl-tRNA and aminoacyl-tRNA, are crucial for the reaction to proceed rapidly and efficiently. Here, we describe the influence of rRNA interactions with cytidine residues in A-site substrate analogs (C-puromycin or CC-puromycin), mimicking C74 and C75 of tRNA on the reaction. Base-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 32 publications
5
24
0
Order By: Relevance
“…The effect of two protons or one proton was observed for C-puromycin at 37°C (30) or 20°C (31), respectively. Furthermore, the rate of peptidyl transfer to CC-puromycin displayed a qualitatively different and much weaker pH-dependence (30).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The effect of two protons or one proton was observed for C-puromycin at 37°C (30) or 20°C (31), respectively. Furthermore, the rate of peptidyl transfer to CC-puromycin displayed a qualitatively different and much weaker pH-dependence (30).…”
Section: Discussionmentioning
confidence: 96%
“…In fact, the pH-dependence of the peptidyl transfer reaction has previously been observed only for small aa-tRNAanalogs, like puromycin, C-puromycin, CC-puromycin (23,30,31), or puromycin analogs (32). For these, the pH-dependence is complex, with the effect of two protons on the rate of peptidyl transfer to puromycin at 37°C (23,30) as well as at 20°C (31). The effect of two protons or one proton was observed for C-puromycin at 37°C (30) or 20°C (31), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Any effect EF-P may have on translocation or on the transition of the ribosome-bound tRNAs to the hybrid states would not be seen by monitoring puromycin reactivity. Furthermore, puromycin does not contain the critical tRNA residues needed for the ratelimiting accommodation step in the A-site (31). It was previously shown that EF-P also affects the rate of reaction between a P-site tRNA and CA-amino acids, which mimic the 3Ј end of an aminoacylated tRNA, but only in the case of small amino acids (32).…”
Section: Discussionmentioning
confidence: 99%
“…At low concentrations, binding of C-Pmn to the A site appeared to be rate-limiting (data not shown), precluding its use at an affordable concentration. The reaction rate with the longer model substrate CC-Pmn (puromycin derivative corresponding to the complete aminoacylated CCA terminus linked to O-methyltyrosine) or the full-length substrate aminoacyl-tRNA on the 70 S ribosome is partially or completely limited by accommodation in the A site (10,35,36), which makes it difficult to interpret the results for the following peptidyl transfer reaction.…”
Section: Rate Constants Of Pmn Reaction With Differentmentioning
confidence: 99%